Populist seduction in Latin America - Torre, Carlos de la (Carlos de la Torre Espinosa) (Research in international studies. Latin America series, 2010)
Is Latin America experiencing a resurgence of leftwing governments, or are we seeing a rebirth of national-radical populism? Are the governments of Hugo Chávez, Evo Morales, and Rafael Correa becoming institutionalized as these leaders claim novel models of participatory and direct democracy? Or are they reenacting older traditions that have favored plebiscitary acclamation and clientelist distribution of resources to loyal followers? Are we seeing authentic forms of expression of the popular will by leaders who have empowered those previously disenfranchised? Or are these governments as ch.